A SYSTEMATIC LITERATURE REVIEW OF FACTORS INFLUENCING PURCHASE INTENTION ON SOCIAL ENTERPRISE PRODUCTS - Zhen-Yee Tan; Jeffrey Cheah (Journal of Islamic, Social, Economics and Development, 2022)
Social enterprise is a hybrid entity that applies a business model to achieve financial value while pursuing a social or environmental agenda. However, the development of a social enterprise in many developing countries like Malaysia is still not mature, where most of them face a survival crisis due to financial difficulties. Social entrepreneurs need to comprehend the factors that might affect the purchase intention of their customers. Thus, this study established a systematic review, content analysis, and gap analysis method to identify and conceptually framing the most prevalence variable that determines the customer purchase intentions. First, 20 core articles were selected from 1,576 articles that published in indexed journals. Next, an in-depth content analysis was established to reveal the most prevalence variables that chosen and examined in the past empirical research. Hereafter, this study validated each variable based on the commonly used theory, namely the Theory of Planned Behaviour, in explaining and predicting the decision-making process of product purchasing. Subsequently, a gap analysis was established to explore important empirical findings in the previous studies and determine the contradictory evidence and knowledge gaps. The research findings could be a practical guide for social entrepreneurs in constructing their marketing strategies to increase their revenue. Consequently, by improving the social enterprise's performance, it will help address social and environmental issues. Future studies might extend this study by empirically examine the model in a different context.